KEWENANGAN DEWAN KEHORMATAN PENYELENGGARA PEMILIHAN UMUM MENGADILI PENYALAHGUNAAN WEWENANG PENYELENGGARAAN PEMILU - I Nyoman Sugiarta,; I Nyoman Suandika,; Kadek Dedy Suryana, (Nusantara Hasana Journal, 2024)
The purpose of this research is to analyze the authority to adjudicate abuse of authority, as well as to understand the practice of adjudicating complaints of abuse of authority by the Honorary Council of General Election Organizers. The method used in preparing this research is a juridical-normative approach, namely research that focuses or examines the application of legal norms or rules in positive law. Apart from that, juridical-normative research focuses on library materials and regulations used as basic materials for preparation. The results of this research are that the provisions on abuse of authority norms in Article 15 letter (d) of DKPP Regulation Number 2 of 2017 have absorbed the concept of abuse of authority in election administration law. From a theoretical perspective, the concept of abuse of authority is usually only limited to the perspective of legal actions/factual actions of government administration, so that it does not become an object of study in ethical assessments/trials. From the juridical aspect, the provisions of Article 15 letter (d) normatively conflict with Article 21 of the AP Law which states that the Court (Administration) has the authority to judge whether there are elements of abuse of authority, so that systematically assessing whether there are elements of abuse of authority is the domain of the State Administrative Court or Bawaslu which is a quasi judiciary in the field of election administration, as stated in Article 460 of the Election Law. Furthermore, the assessment of the actions and actions of election organizers who are deemed to have committed abuses of authority cannot be based on ethical standards, because authority is the core object of study in state administrative law. In other words, Article 15 letter (d) of DKPP Regulation Number 2 of 2017 must be deleted.